GERAKAN PANGAN MURAH DI KECAMATAN MEDAN TUNTUNGAN KOTA MEDAN - Stella Sipayung; Emi Triani; Fajar Utama Ritonga (CV SWA Anugerah, 2023)
This journal reviews food movement activities carried out in Medan Tuntungan District, Medan City. This research aims to describe its implementation and impact on the surrounding community. This type of research uses a method of collecting data through observation and analysis of related documents. The results of the research show that the cheap food movement has had many impacts on the surrounding population. The implementation process was carried out by the Medan Tuntungan District Head's Office, part of the Social Welfare section in the hall of the Medan District Head's Office by contacting the village head or environmental head of each sub-district to make an announcement regarding the cheap food movement to the community. The impact of this food movement is that underprivileged people still get quality food.